2023
DOI: 10.1021/acs.accounts.3c00286
|View full text |Cite
|
Sign up to set email alerts
|

MA’AT Analysis: Probability Distributions of Molecular Torsion Angles in Solution from NMR Spectroscopy

Abstract: Metrics & MoreArticle Recommendations CONSPECTUS: Monosaccharides adopt multiple conformations in solution, and this structural complexity increases significantly when they are assembled into oligosaccharides and polysaccharides. Characterization of the conformational properties of saccharides in solution by NMR spectroscopy has been hampered by several complicating factors, including difficulty interpreting spectra because of significant signal overlap, population averaging of NMR parameters, and unique prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…MA’AT analysis has been applied successfully to treat single-state conformational behaviors involving O -glycosidic linkages, and N - and O -acetyl side-chains, in mono-, di-, and oligosaccharides. Pertinent to the present work, the MA’AT method has been tested recently for its ability to treat multi-state conformational equilibria through investigations of the pseudorotational properties of aldopentofuranosyl rings . This work showed that MA’AT analysis provides reliable unbiased models of N / S ring conformational equilibria and revealed discrepancies between MA’AT -derived models of solution behavior and those predicted by MD simulation.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…MA’AT analysis has been applied successfully to treat single-state conformational behaviors involving O -glycosidic linkages, and N - and O -acetyl side-chains, in mono-, di-, and oligosaccharides. Pertinent to the present work, the MA’AT method has been tested recently for its ability to treat multi-state conformational equilibria through investigations of the pseudorotational properties of aldopentofuranosyl rings . This work showed that MA’AT analysis provides reliable unbiased models of N / S ring conformational equilibria and revealed discrepancies between MA’AT -derived models of solution behavior and those predicted by MD simulation.…”
Section: Discussionmentioning
confidence: 80%
“…The present work describes a radical departure from prior NMR treatments of this problem in those ensembles of NMR J -couplings that show strong dependencies on ω are used collectively to obtain continuous rotameric models of ω independent of assumptions about the nature of the rotameric distribution and independent of energetic bias. NMR data alone are used to calculate probability distributions of ω using MA’AT analysis. , No theoretical (calculational) input is required, although theoretical calculations play a central role in J -coupling equation parametrization whose reliability is key to the success of the method. Fortunately, DFT-calculated J -values can be validated experimentally, thus eliminating or at least reducing the errors and uncertainties associated with these calculations.…”
Section: Discussionmentioning
confidence: 99%
“… MA’AT analysis was then applied to these J -couplings in 3 to obtain mean values of the ϕ and ψ that comprise its linkage (Scheme ) and their circular standard deviations (CSDs) to gain insight into their librational averaging. The advantage of MA’AT analysis for this comparison is the ability of the method to provide experiment-based probability distributions of molecular torsion angles in solution and to give mean angles with high precision and accuracy. Evidence of significant differences in the linkage conformations in 1 and 3 would support the argument that inter-residue hydrogen bonding plays a role in dictating preferred linkage conformation in aqueous solution, whereas identical (or near identical) conformations would suggest that this hydrogen bonding, if persistent in solution, is not a major determinant of linkage conformation. The results of these studies are described in this report.…”
Section: Introductionmentioning
confidence: 94%
“…Conformationally dependent 1 J CH , 1 J CC , 2 J CH , 2 J CC , and n J CC coupling constants can be used as a complement and with a set of redundant NMR couplings the conformation or conformational equilibria of oligosaccharides in solution can be investigated using single-state and multistate models to determine rotamer population distributions (MA'AT analysis). 39,40 An alternative, still relying on that only certain nuclei are 13 Clabeled is to use uniform [UL- 13 C 6 ]-labeling of one or more specific sugar residue(s) in an oligosaccharide, a labeling scheme that may give access to a large number of spin−spin coupling constants but also to that other NMR parameters can be measured. The power of automated glycan synthesis was shown for a series of a compounds, viz., a β-(1 → 6)-linked hexaglucoside, 13 C isotopologues thereof and 19 F analogues.…”
Section: ■ Shape (Conformation) and Motions (Dynamics)mentioning
confidence: 99%
“…in small oligosaccharides), will give the complete set of three-bond coupling constants across the glycosidic linkage. Conformationally dependent 1 J CH , 1 J CC , 2 J CH , 2 J CC , and n J CC coupling constants can be used as a complement and with a set of redundant NMR couplings the conformation or conformational equilibria of oligosaccharides in solution can be investigated using single-state and multistate models to determine rotamer population distributions ( MA’AT analysis). , …”
Section: Shape (Conformation) and Motions (Dynamics)mentioning
confidence: 99%